Cable Bacteria and the Bioelectrochemical Snorkel: The Natural and Engineered Facets Playing a Role in Hydrocarbons Degradation in Marine Sediments - Matturro, Bruna; Cruz Viggi, Carolina; Aulenta, Federico; Rossetti, Simona (Frontiers in Microbiology, 2017)
The composition and metabolic traits of the microbial communities acting in an innovative bioelectrochemical system were here investigated. The system, known as Oil Spill Snorkel, was recently developed to stimulate the oxidative biodegradation of petroleum hydrocarbons in anoxic marine sediments. Next Generation Sequencing was used to describe the microbiome of the bulk sediment and of the biofilm growing attached to the surface of the electrode. The analysis revealed that sulfur cycling primarily drives the microbial metabolic activities occurring in the bioelectrochemical system. In the anoxic zone of the contaminated marine sediment, petroleum hydrocarbon degradation occurred under sulfate-reducing conditions and was lead by different families of Desulfobacterales (46% of total OTUs). Remarkably, the occurrence of filamentous Desulfubulbaceae, known to be capable to vehicle electrons deriving from sulfide oxidation to oxygen serving as a spatially distant electron acceptor, was demonstrated. Differently from the sediment, which was mostly colonized by Deltaproteobacteria, the biofilm at the anode hosted, at high extent, members of Alphaproteobacteria (59%) mostly affiliated to Rhodospirillaceae family (33%) and including several known sulfur- and sulfide-oxidizing genera. Overall, we showed the occurrence in the system of a variety of electroactive microorganisms able to sustain the contaminant biodegradation alone or by means of an external conductive support through the establishment of a bioelectrochemical connection between two spatially separated redox zones and the preservation of an efficient sulfur cycling.